Multiple Intelligence-based Instruction to Increase Students’ Intrinsic Motivation in Learning English - Kartika Indah Permata; Rheyna Salsabilla; Md. Sikandar Ali (Universitas Muhammadiyah Semarang, 2023)
The one-for-all approach has long been a concern in the educational field as it influences learners’ learning capacity negatively. However, it is still practiced by many teachers in Indonesia. This study aims to investigate the effectiveness of Multiple Intelligence-based instruction to increase students’ intrinsic motivation in learning English. It used a quasi-experiment design, and the participants were 40 non-English department students in UIN Walisongo Semarang that were selected using purposive sampling. Activity Perception Questionnaire from Intrinsic Motivation Inventory was used to measure students’ experience of given activities. Analyzed using Mann-Whitney U test, it was found that Multiple Intelligence-based instruction was effective to enhance the value or usefulness, interest, and perceived choice of students. These aspects were critical in the process of internalization and integration, which led to higher intrinsic motivation.